Media Interaktif Pembelajaran Sistem Pernapasan Manusia - Ganiartha, Irvan Putra; Liliana, Liliana; Purba, Kristo Radion (Jurnal Infra, 2015)
Lessons learned in the field of biology like human breathing often becomes a tough lesson to understand because in biology lessons often rely solely on pictures in the textbooks, while students can sometimes interpret the picture differently. One way to understand the biology of the concept could use multimedia applications these applications would pack the human respiratory system become lessons interactive and engaging, where users will be involved in the learning process.The material in this interactive media among others are breathing and respiratory phase, respiratory organs, respiratory gas transport mechanisms in the alveoli and respiratory disease. There is also a test to measure the level of understanding the user that has been studied from this application. Applications created by using Adobe Flash CS6.Simulation and animation in the application will greatly assist the user in understanding the material. Therefore userâs interest in learning is increased, coupled with the easiness of application usage and user friendly